2015
DOI: 10.3201/eid2108.141891
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Viruses of Human Origin in Swine, Brazil

Abstract: Multiple divergent lineages challenge the design of cross-protective vaccines and highlight the need for additional surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 37 publications
3
74
0
3
Order By: Relevance
“…In addition to these named subdivisions, the 1B.2 clade from 2010 to the present contained sporadic human-to-swine transmission episodes ( n = 7) in Argentina, Chile (36), China, Mexico, and Vietnam; these spillovers did not warrant the designation of a clade either due to failure to establish in swine populations or due to insufficient numbers to meet our criteria. Similarly, 1B.2.2 (22) included viruses collected from spatially isolated swine populations in Argentina and Brazil (23) and in Mexico that represent human-to-swine transmission episodes, but the number of viruses is too low to be able to confidently infer a separate clade. To link these viruses to their source population and maintain flexibility should additional surveillance detect more samples, we classified these viruses as “Other-Human.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these named subdivisions, the 1B.2 clade from 2010 to the present contained sporadic human-to-swine transmission episodes ( n = 7) in Argentina, Chile (36), China, Mexico, and Vietnam; these spillovers did not warrant the designation of a clade either due to failure to establish in swine populations or due to insufficient numbers to meet our criteria. Similarly, 1B.2.2 (22) included viruses collected from spatially isolated swine populations in Argentina and Brazil (23) and in Mexico that represent human-to-swine transmission episodes, but the number of viruses is too low to be able to confidently infer a separate clade. To link these viruses to their source population and maintain flexibility should additional surveillance detect more samples, we classified these viruses as “Other-Human.”…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge was the forced inclusion of viruses with likely specific regional evolutionary histories into a geographically broader classification because of the paucity of sequences from that region. For example, a small cluster of distinct human seasonal viruses in Brazil (23) were classified as 1B.2.2 although they differed from other 1B.2.2 viruses that circulate in different geographic regions. A unique clade designation for this handful of Brazil viruses might be considered if phylogenetic support was >70% and if additional evidence demonstrated continued circulation of this genetic grouping, such as specific hemagglutination inhibition serosurveillance data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the passive monitoring of influenza A viruses in pigs has taken place since 2009 ( 8 ). Recently, a phylogenetic study revealed that H1N2 subtype viruses have circulated undetected in swine herds in Brazil for more than a decade, and reassortments may have occurred ( 9 ). These viruses seem to be reassortants originating from an ancestor virus introduced to pigs from humans in the late 1990s and early 2000s and remained as a relic from a now-extinct human-host hemagglutinin lineage.…”
mentioning
confidence: 99%
“…These viruses seem to be reassortants originating from an ancestor virus introduced to pigs from humans in the late 1990s and early 2000s and remained as a relic from a now-extinct human-host hemagglutinin lineage. However, after the emergence in humans of influenza A(H1N1)pdm09 in 2009, reassortment events lead to H1N2 viruses acquiring internal genes segments from the pandemic strain ( 9 ). …”
mentioning
confidence: 99%